THE ROLE AND EFFECTIVENESS OF DIGITAL HR SOLUTIONS IN HUMAN RESOURCE MANAGEMENT IN EDUCATIONAL INSTITUTIONS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This thesis analyzes the role and significance of digital HR solutions in managing human resources within educational institutions. The study highlights how technology-driven HR management systems contribute to improving the quality and efficiency of education. Particular attention is given to the advantages of modern HR platforms in digital monitoring of teachers’ performance, objective evaluation of effectiveness, analysis of competencies, and the development of motivational mechanisms. Furthermore, the paper explores how digital HR solutions support teachers’ professional growth, help identify individual development trajectories, and enhance work performance. The findings substantiate the relevance of digital approaches in modernizing human resource management in the education sector.